The Application of Multimedia Teaching in Primary School Classroom - Ye, Xinnan (Transactions on Social Science, Education and Humanities Research, 2024)
With the rapid development of science and technology, multimedia teaching has become one of the important trends in the field of education. This paper thoroughly explores multimedia teaching in primary school classrooms, focusing on its significance, advantages, and challenges. Multimedia teaching plays a pivotal role in enhancing the educational experience for young learners. Through an in-depth analysis of literature and case studies, this research highlights its profound impact. Multimedia resources, including interactive digital content, videos, and animations, can engage students, enhance comprehension, and create interactive learning environments, fostering intellectual development. However, implementing multimedia teaching is not without obstacles. This study exposes difficulties with using multimedia effectively and how to mix it with traditional teaching methods. To offer practical insights, the study showcases effective approaches and solutions in multimedia education by examining examples of useful methods. Teachers’ perspectives on how to select multimedia, convey information reasonably, and develop multimedia literacy are presented. In conclusion, this paper sets the foundation for the use of multimedia in primary school instruction in the future. It offers practical suggestions for teachers and researchers to improve and broaden the use of multimedia tools, thereby boosting the educational experiences of young pupils.